Too old to work, too young to retire? - Andrea Ichino; Guido Schwerdt; Rudolf Winter-Ebmer; Josef Zweimüller (Center for Economic Studies and ifo Institute (CESifo), 2007)
We use firm closure data from social security records for Austria 1978-1998 to investigate the effect of age on employment prospects. We rely on exact matching to compare workers displaced due to firm closure with similar non-displaced workers. We then use a difference-in-difference strategy to analyze employment and earnings of older relative to prime-age workers in the displacement and non-displacement groups. Results suggest that immediately after plant closure the old have lower re-employment probabilities as compared to prime-age workers but later they catch up. While among the young the employment prospects of the displaced remain persistently different from those of the non-displaced, among the old the effect of displacement fades away, and actually disappears even immediately after plant closure when the effect of tenure based severance payment is controlled for. Our evidence suggests that increasing the retirement age does not necessarily produce individuals who are too old to work but too young to retire.
Keywords: J14; J65; 330; aging; employability; plant closures; matching; Alternde Bevölkerung; Flexible Altersgrenze; Arbeitsnachfrage; Arbeitsangebot; Schätzung; Österreich